Torefaksi Pelepah Sawit : Pengaruh Kondisi Proses Terhadap Nilai Kalor Produk Torefaksi - Wenny Susanty; Zuchra Helwani; Zulfansyah Zulfansyah (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Palm frond is biomass that has not been widely used as a renewable energy source. Torrefaction is a pretreatment process to improve the quality of the biomass as solid fuel. The aim of this research was to determine the condition of the process to the increase in calorific value torrefaction product. Results of the research is the calorific value and the proximate analysis torrefaction products such as moisture content, ash content, volatile content, and the content of fixed carbon. Torrefaction product calorific value in the range 17.700-19.800 kJ/kg.Key words: biomass, oil palm frond, renewable energy, solid fuel, torrefaction,